2021
DOI: 10.3390/ijms23010073
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TRIP6, ABCC3 and CPS1 Expression in Resistance of Ovarian Cancer to Taxanes

Abstract: The main problem precluding successful therapy with conventional taxanes is de novo or acquired resistance to taxanes. Therefore, novel experimental taxane derivatives (Stony Brook taxanes; SB-Ts) are synthesized and tested as potential drugs against resistant solid tumors. Recently, we reported alterations in ABCC3, CPS1, and TRIP6 gene expression in a breast cancer cell line resistant to paclitaxel. The present study aimed to investigate gene expression changes of these three candidate molecules in the highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The combined regimen composed of PTX with both third generation taxanes, used in the present study, caused downregulation of CPS1 in the PTX-resistant NCI/ADR-RES-derived mouse xenograft model in vivo . Furthermore, CPS1 overexpression was also associated with poor survival of patients with epithelial ovarian carcinoma ( Seborova et al, 2022 ). We therefore assume that a detailed study of effects of taxanes and their combinations on the gene expression profile (and potentially also epigenetic factors) may help decipher not only the mechanisms behind their antitumor activity, but also reveal new candidate biomarkers and/or targets enabling personalized therapy of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The combined regimen composed of PTX with both third generation taxanes, used in the present study, caused downregulation of CPS1 in the PTX-resistant NCI/ADR-RES-derived mouse xenograft model in vivo . Furthermore, CPS1 overexpression was also associated with poor survival of patients with epithelial ovarian carcinoma ( Seborova et al, 2022 ). We therefore assume that a detailed study of effects of taxanes and their combinations on the gene expression profile (and potentially also epigenetic factors) may help decipher not only the mechanisms behind their antitumor activity, but also reveal new candidate biomarkers and/or targets enabling personalized therapy of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the differences in the mechanism of action of both therapies. On one hand, in CT, PX must reach the cell cytoplasm to exert its stabilizing effect on microtubules [ 67 , 68 ], so it can be extruded by ABCG2 proteins [ 69 , 70 ] or metabolized by CYP proteins [ 65 ]. On the other hand, when PX and Carb are administered in a metronomic scheme, they exert a pro-apoptotic effect by the activation of mAchRs, which are present in the cell membrane [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPS1 (Carbamoyl-Phosphate Synthase 1) encodes a crucial mitochondrial enzyme that catalyzes the synthesis of carbamoyl phosphate in the urea cycle. Several recent studies showed the associations of CPS1 with some cancers such as gastric cancer and ovarian cancer [ 73 , 74 ]. Two recent published studies showed that the expression level of CPS1 was upregulated in LUAD tissue, and its high expression resulted in a poor survival rate [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%